2006
DOI: 10.1152/ajpheart.00808.2005
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of mesenteric lymph isolated from rats with burn injury on contractile function in rat ventricular myocytes

Abstract: Dual effects of mesenteric lymph isolated from rats with burn injury on contractile function in rat ventricular myocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…More recently, our studies have shown that the mesenteric lymph collected from rats with Ϸ40% TBSA burn injury (burn lymph) exerted concentration-dependent effects on the contractility of LV myocytes isolated from healthy rats. At lower concentrations (Ͻ0.5%), burn lymph increased the amplitude of myocyte contraction (38), whereas physiologically relevant concentrations (0.1-5%) of burn lymph reduced myocyte contractility (37). Taken together, these observations strongly suggest that burn injury promotes the mobilization or release of factor(s) in mesenteric lymph, which trigger abnormal myocyte contractility and that defective cardiomyocyte contractility contributes to burn-related cardiac depression.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…More recently, our studies have shown that the mesenteric lymph collected from rats with Ϸ40% TBSA burn injury (burn lymph) exerted concentration-dependent effects on the contractility of LV myocytes isolated from healthy rats. At lower concentrations (Ͻ0.5%), burn lymph increased the amplitude of myocyte contraction (38), whereas physiologically relevant concentrations (0.1-5%) of burn lymph reduced myocyte contractility (37). Taken together, these observations strongly suggest that burn injury promotes the mobilization or release of factor(s) in mesenteric lymph, which trigger abnormal myocyte contractility and that defective cardiomyocyte contractility contributes to burn-related cardiac depression.…”
mentioning
confidence: 83%
“…Rats were deeply anesthetized (60 mg/kg pentobarbital sodium), and the heart from each rat was quickly removed as previously described (37,38). The heart was cannulated and perfused in a retrograde fashion via the aorta by the Langendorff method for about 3 min with a modified Ca 2ϩ -free Krebs-Henseleit solution containing (in mmol/l): 110 NaCl, 2.6 KCl; 1.2 MgCl 2, 1.2 KH2PO4, 25 NaH 2PO4, 11 glucose, 30 taurine, and 10 HEPES (pH 7.4), which was oxygenated by bubbling with 95% O 2-5% CO2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we do not know what the biologically active factors are in T/HS lymph, we have excluded a number of putative candidates, including cytokines (9), bacteria, and bacterial products (2). Whatever the factors are in lymph, on the basis of our in vitro burn studies, burn lymph appears to exert a direct depressant effect on normal myocyte contractility and Ca 2ϩ transients that are similar to the changes observed in myocytes harvested from burned rats (39). Further studies investigating the effects of T/HS lymph on in vivo cardiac and in vitro myocyte contrac- Values are means Ϯ SE; n ϭ no.…”
Section: Discussionmentioning
confidence: 99%